Analisis Fiqih Siyasah terhadap Kebijakan Bantuan Sosial: Perspektif Kemaslahatan Umat dan Politik Elektoral - Fatimatuz Zahroil Batul (Ma'had Aly Raudhatul Ma'arif, 2026)
Social assistance (bansos) is a principal instrument of the Indonesian government for poverty alleviation. The social protection budget rose from IDR 431.5 trillion in 2022 to IDR 508.2 trillion in the 2026 draft. Comparative data for 2022–2025, however, indicate that this budgetary increase did not proportionally accelerate poverty reduction and instead shows a sharp rise coinciding with the 2024 general election cycle, raising suspicion of electoral motives behind the policy. This study analyzes Indonesia’s social assistance policies for 2022–2026 through the lens of fiqh siyasah, focusing on the concepts of ummah, siyasah ‘adilah, tamkin, and amanah. Employing a normative-qualitative method with a library-research approach, the study examines official data from the Central Statistics Agency and the Ministry of Finance, corroborated with media reports, classical and contemporary fiqh siyasah literature, and related scientific studies. Findings reveal that the social protection budget increased by 12 percent in the 2024 election year compared to the previous year and was accompanied by indications of program personalization and disbursement scheduling aligned with campaign stages and voting day. Such electoralized distribution conflicts with the principles of maslahah mursalah and siyasah ‘adilah in fiqh siyasah, which prioritize comprehensive and sustainable public welfare. The persistence of beneficiary dependency, stemming from insufficient empowerment (tamkin) programs, violates the principle of kifayah. Moreover, the politicization of social assistance constitutes an abuse of leadership trust (amanah), neglecting the ruler’s moral responsibility toward the people, despite the budget’s procedural approval by the legislature. The study concludes that aligning social protection policies with fiqh siyasah principles requires depoliticized, empowerment-oriented, and sustainably targeted interventions to realize equitable maslahah for the ummah.